Rationality of Education for Out of School Children in the Akit Community in Bantan District, Bengkalis Regency - Risdayati Risdayati; Mita Rosaliza (Budapest International Research and Critics University, 2022)
This research will be conducted in Bantan District, Bengkalis Regency, where the Akit Tribe is domiciled. The purpose of this study is to analyze how the rationality construction of school dropouts in the Akit Tribe community, Purposive is used in this study and to determine the criteria of the research subject as a source of information in this study, key informants will be determined such as the village head of Berancah, Batin or the traditional chief of the Tribe. Akit, the Principal at SD Berancah, and the surrounding community who will also be triangulated to get more complete information. Informants in this study will determine which children who have dropped out of school will be taken from secondary data from the school. The analysis of this study uses a qualitative descriptive by interviewing the research subjects in depth.